Electrofishing efficiency in low conductivity neotropical streams: towards a non‐destructive fish sampling method. (25th April 2014) - Allard, L.; Grenouillet, G.; Khazraie, K.; Tudesque, L.; Vigouroux, R.; Brosse, S.
Abstract Rotenone sampling is the most efficient method for assessing the fish assemblage structure and species abundance of low conductivity Amazonian streams. It does, however, cause fish mortality and disturb aquatic ecosystem. The aim of this study was to search for a non‐destructive alternative. The efficiency of electrofishing was compared against complete removal using rotenone. This procedure was repeated in 12 streams dispersed throughout French Guiana to test for environmental and biological effects such as water conductivity, stream depth, fish family membership and body size. This study revealed that the efficiency of electrofishing was influenced by stream conductivity and stream depth, but not by fish family or body size. The electrofishing method might constitute an efficient alternative to using rotenone in smaller streams (below 25‐cm depth and above 43 μS cm−1), whereas in deeper and/or slightly conductive streams, rotenone still remains the only method able to provide a quick and comprehensive picture of the fish assemblage.